The awareness of labour in safety and health on site / Eizanizam Muhammad Eng. - Muhammad Eng, Eizanizam (2006)
Industry awareness towards health and safety regulations and its implementation is becoming more critical and more pressing particularly on the construction personnel side. This can be seen by the enactments of the Occupational Safety and Health Act 1994, the coverage of which extends to most workplaces in the country. As a result there is increasing of the training and education on occupational safety and health particularly to construction personnel's workforce. This research will try to investigate the major problem and study the safety and health on workplace. This research also covers the study on the factors contributing to accidents & near-misses.